Duckling diary - Baglio, Ben M.; Speirs, John (New York : Scholastic, 2000)
Mandy tries to hatch a duck's egg left in an abandoned nest.
"A Little Apple paperback."
3.8
3-6.
Keywords: Ducks -- Fiction; Animals -- Treatment -- Fiction; Ducks -- Fiction; Animal welfare -- Fiction